UPAYA INTERNATIONAL CAMPAIGN TO BAN LANDMINES (ICBL) UNTUK MENGHAPUS PRODUKSI DAN PENGGUNAAN RANJAU DARAT - Ali Muhammad; Sidiq Kurniawan (UNIDA Gontor, 2022)
This article analyzes the efforts made by the International Campaign to Ban Landmines (ICBL) in realizing a landmine-free world. In particular, this article examines the role of the ICBL to establish a regime for the prohibition of landmines—known as the Ottawa Convention. The birth of the regime for the prohibition of landmines cannot be separated from the role of various parties, especially ICBL, which are the driving force of this movement. In addition, there is also support from countries, such as Canada. The ICBL continues to strive to build the regime and, to date, most of the countries in the world have already ratified the convention. Altghouh obstacles remain, ICBL and its partners continues to build a world which is free from landmines.